Sperm production and quality in European eel (Anguilla anguilla) in relation to hormonal treatment. Issue 12 (8th September 2021) - Koumpiadis, Paraskevas; Sganga, Daniela E.; Politis, Sebastian N.; Gallego, Victor; Butts, Ian A. E.; Asturiano, Juan F.; Batjakas, Ioannis E.; Tomkiewicz, Jonna
Abstract: Aquaculture production relies on controlled management of gametogenesis, especially in species where assisted reproduction is needed for obtaining gametes in captivity. The present study used human chorionic gonadotropin (hCG) treatments to induce and sustain spermatogenesis in European eel ( Anguilla anguilla ). The aim was to evaluate effects of strip‐spawning timing (12 vs. 24 hr) after weekly administration of hCG and the necessity of a primer dose (in addition to weekly hormonal treatment) prior to strip spawning (primer vs. no‐primer) on sperm quality parameters. Sperm parameters included milt production (weight), density and sperm kinematics at Week 9, 11 and 13 after onset of treatment. Spermiation commenced in 11.5% of males in Week 5 and by Week 9, and all males produced milt. Male weight, milt production, sperm density and spermatocrit did not differ among hormonal treatments during the experimental period. Overall, male weight decreased from 106.3 to 93.0 g, milt weight increased from 3.5 to 5.4 g, sperm density counts decreased from 11.7 × 10 9 to 10.5 × 10 9 cells/ml, and spermatocrit decreased from 46.5% to 40.5%. Furthermore, spermatocrit was positively related to haemocytometer counts ( R 2 = .86, p < .001), providing a reliable indicator of sperm density. Differences in sperm kinematics were observed depending on strip‐spawning timing after hormonal injection (12 vs. 24 hr) but with no consistent pattern. These sperm quality parameters also did not consistently differ between the no‐primer and primer treatments. Considering that each male may be stripped 4–5 times over the 2–3 months spawning season, omitting the primer would reduce animal handling, material costs and labour intensity, while sustaining high‐quality sperm production.